Immune regulatory adjuvant approach to mitigate subcutaneous immunogenicity of monoclonal antibodies - Nicole L. Jarvi; Manali Patel; Krithika A. Shetty; Nhan H. Nguyen; Brooke F. Grasperge; Donald E. Mager; Donald E. Mager; Robert M. Straubinger; Sathy V. Balu-Iyer (Frontiers in Immunology)
IntroductionImmunogenicity continues to be a challenge for development and clinical utility of monoclonal antibodies, and there are gaps in our current ability to prevent anti-drug antibody development in a safe and antigen-specific manner.MethodsTo mitigate immunogenicity of monoclonal antibodies administered subcutaneously, O-phospho-L-serine (OPLS)—the head group of the tolerance-inducing phospholipid, phosphatidylserine—was investigated as an immunoregulatory adjuvant.ResultsFormulations of adalimumab, trastuzumab or rituximab with OPLS showed reduction in relative immunogenicity in mice compared to vehicle formulations, indicated by reduced anti-drug antibody development and significant reductions in CD138+ plasma cell differentiation in bone marrow. Titer development toward recombinant human hyaluronidase, a dispersion enhancer that was co-formulated with monoclonal antibodies, was similarly reduced. Subcutaneous administration of adalimumab with OPLS resulted in a two-fold increase in expression of type 1 regulatory (Tr1) T cell subset in the spleen. This is consistent with in vitro studies where co-culturing of dendritic cells primed with ovalbumin in the presence and absence of OPLS and antigen specific T-cells induced expression of Tr1 phenotype on live CD4+ T cells.ConclusionThis adjuvant does not impact immune competence of non-human primates and mice, and repeated administration of the adjuvant does not show renal or hepatic toxicity. Formulation of monoclonal antibodies with the immunoregulatory adjuvant, OPLS, was found to be safe and effective at mitigating immunogenicity.